2020
DOI: 10.1111/ajco.13504
|View full text |Cite
|
Sign up to set email alerts
|

Advances and challenges of neoadjuvant therapy in pancreatic cancer

Abstract: Pancreatic cancer has been becoming the second cause of cancer death in the western world, and its disease burden has increased. Neoadjuvant therapy is one of the current research hotspots in the field of pancreatic cancer, aiming to improve the surgical rate and prognosis of pancreatic cancer. Based on the latest evidence, this review discussed neoadjuvant therapy in pancreatic cancer from the following three aspects: patient selection, protocols selection of neoadjuvant therapy, and treatment response evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 88 publications
2
9
0
5
Order By: Relevance
“…Our study showed that the expression of the immunohistochemical markers Maspin, IMP3, S100A, S100P, and TFFs is significantly different in PDAC, as compared with nonneoplastic pancreatic conditions, in accordance with previous studies. 11,[14][15][16]22 In the present study, we found that all markers were unreactive on nonneoplastic samples, while a variable reactivity was obtained in neoplastic ones. In the 3 samples in group 1, all immunohistochemical markers were negative, and the final diagnosis on the surgical sample was of chronic pancreatitis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our study showed that the expression of the immunohistochemical markers Maspin, IMP3, S100A, S100P, and TFFs is significantly different in PDAC, as compared with nonneoplastic pancreatic conditions, in accordance with previous studies. 11,[14][15][16]22 In the present study, we found that all markers were unreactive on nonneoplastic samples, while a variable reactivity was obtained in neoplastic ones. In the 3 samples in group 1, all immunohistochemical markers were negative, and the final diagnosis on the surgical sample was of chronic pancreatitis.…”
Section: Discussionsupporting
confidence: 57%
“…9,12,13 In addition, standard imaging techniques, including CT and MRI, can be inconclusive when attempting to distinguish the 2 types of lesions. 12,13 Recent studies reported the potential of neoadjuvant therapy to decrease the size of pancreatic tumors and make them more resectable, 14 thus improving the outcome. In this situation, a rapid and accurate diagnosis on FNAB of a pancreatic mass is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor tissue acquisition pretreatment (via biopsy) and at surgery offers a unique opportunity to observe the intratumoral changes in the tumor and TME after various treatment regimens. 165,166 A recent analysis by Farren et al 167 that examined gene expression and spatial distribution of numerous immunologically relevant cells and proteins showed distinct differences in resected tumors from untreated pancreatic tumors vs tumors treated with neoadjuvant therapy. As a retrospective study, the relevance of these changes to patient outcome and response to further adjuvant therapy are not addressed; however, the results indicate further research in this area is needed.…”
Section: Treatment Based On Disease Stagementioning
confidence: 99%
“…NAT is now one of the most commonly used treatments for cancer and has a wide range of clinical applications in the areas of pancreatic cancer, breast cancer, gastric cancer, colorectal cancer, and cholangiocarcinoma (56)(57)(58)(59). To improve clinical prognosis and outcomes, NAT has also been introduced to the treatment of EC, especially for patients with locally advanced EC.…”
Section: Neoadjuvant Treatmentmentioning
confidence: 99%